Historical Investigation of the Social Role of Lady Hamidah Mosaffa; Imam Kazem’s Mother - Naahid Tayyebi (تاریخ اسلام)
Mothers of Imams are considered as the most influential persons in the period of Imams (PBUT) and since they are the salient example of ‘respectful relatives’, a high position is considered for them. So the study of Lady Hamideh’s life, Imam Kazem’s mother, would be of particular importance and necessity, due to the fact that Imam Baqer and Imam Sadiq (PBUT) have had precious words about her and familiarity with the history of her life can lead to reviewing parts of the history of Islam through a new approach. The present writing has investigated the narrations in regard with Lady Hamideh and familiarity with the personal and characteristic properties, her position in the household of Imamate I addition to her social role considering the present reports in the period of Imam Sadeq and Imam Kazem (PBUT). The most significant reports would be the cases indicating the appointment of this Lady for the contribution of the rights of Medinite people as well as Imam Sadiq (PBUH) delegating her as an authority to respond to the jurisprudential questions and also Imam considering her as successor.